2017
DOI: 10.11648/j.ijll.20170505.13
|View full text |Cite
|
Sign up to set email alerts
|

Verbal Communication Behaviors: How Male and Female University Students Interact in Gendered Talks

Abstract: Abstract:With the existence of language and gender studies emphasizing the male and female dichotomy in interactional strategies, this study aimed to investigate the verbal communication behaviors of language classroom mixed-gender and samegender group conversations involving the same interlocutors. The transcribed data obtained from the three fifteen-minute recorded group interactions indicated that questions and expressions of agreement were the typical behaviors employed by the interlocutors. The results sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 8 publications
4
8
0
Order By: Relevance
“…The lead male and female in this movie showed that there are numerous differences in using language features based on a certain situation. The differences of the use of language by male and female or different gender were also found by Haas (1979), Mulac, et all (1985Mulac, et all ( , 2006, Tepper & Cassidy (1999), Varol & Yilmaz (2010), Gu (2013), andKenneth (2017). In this movie, both lead male and female characters use adjective feature to show their appreciation on the song that they made.…”
Section: Rising Intonation On Declarativessupporting
confidence: 62%
“…The lead male and female in this movie showed that there are numerous differences in using language features based on a certain situation. The differences of the use of language by male and female or different gender were also found by Haas (1979), Mulac, et all (1985Mulac, et all ( , 2006, Tepper & Cassidy (1999), Varol & Yilmaz (2010), Gu (2013), andKenneth (2017). In this movie, both lead male and female characters use adjective feature to show their appreciation on the song that they made.…”
Section: Rising Intonation On Declarativessupporting
confidence: 62%
“…Therefore, the use of fillers by the participants in the conversations may stem not just as a need to stall for time to think, but also to continue the flow of conversation. Furthermore, this study supports Opina's (2017) claim that fillers fill in the silences or gaps in interactions. These suggest why fillers were noticeable in each interaction.…”
Section: Types Of Communication Strategiessupporting
confidence: 87%
“…Females tend to be cooperative in interactions. Females "adhere to a more cooperative speech style" (Chaves as cited in Opina, 2017). Overall, the communication strategies and the characteristics of female speech were used for genuine interaction among the participants.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on gender, men and women are said to use the language differently (Opina, 2017;Vogel, Lopes, & Esposito, 2017;Zhu & Ruan, 2019;Coats, 2019;Wightman, 2020). The sexes often speak virtually different languages, which Tannen (in Mamona, Rubab, Akbar, 2020) has addressed as report talk versus rapport talk.…”
Section: Introductionmentioning
confidence: 99%